2019
DOI: 10.21873/invivo.11683
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Expression of Microglia/Macrophage and Proinflammatory Mediators in Olfactory Bulb and Olfactory Dysfunction After Stroke

Abstract: Background/Aim: Olfactory dysfunction can be caused by stroke but the pathogenesis is still unclear. Previous studies have proved that olfactory dysfunction could be caused by microglia activation in the olfactory bulb and that middle cerebral artery occlusion (MCAO) may induce ipsilateral olfactory bulb microglia activation. This study aimed to explore the possible pathogenesis of ischemic stroke-induced olfactory dysfunction. Materials and Methods: We used a rat model of MCAO to simulate ischemic stroke. Olf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Multiple stereotyped and time-dependent profiles of gene expression were identified within 24 h. As noted in the study, temporally overlapping profiles have the potential to provide a biological "stroke clock" to stroke prevention [89]. Additionally, mRNA expression of genes for inflammatory Iba-1, CD68, CD16 and CD86 proteins was increased in the ipsilateral olfactory bulb compared to the contralateral side 3 days after tMCAO in rats [90]. Recently, gene expression changes in cells during neuroinflammation were identified 24 h after tMCAO using single cell sequencing (scRNA-Seq).…”
Section: Transcriptomics Of Ismentioning
confidence: 64%
“…Multiple stereotyped and time-dependent profiles of gene expression were identified within 24 h. As noted in the study, temporally overlapping profiles have the potential to provide a biological "stroke clock" to stroke prevention [89]. Additionally, mRNA expression of genes for inflammatory Iba-1, CD68, CD16 and CD86 proteins was increased in the ipsilateral olfactory bulb compared to the contralateral side 3 days after tMCAO in rats [90]. Recently, gene expression changes in cells during neuroinflammation were identified 24 h after tMCAO using single cell sequencing (scRNA-Seq).…”
Section: Transcriptomics Of Ismentioning
confidence: 64%
“…This may imply that resting microglia in the olfactory bulb may be triggered by sinonasal inflammation to transform into activated microglia and then secrete inflammatory mediators. 9 The relative mRNA expression levels of pro-inflammatory mediators including IFN-γ, NOS2, MCP-1, and TNF-α in the olfactory bulb were significantly upregulated, while significant downregulation of OMP and NeuN, of marker post-mitotic neurons, was observed in the LPS group. The protein levels of IFN-γ and TNF-α in the olfactory bulb were also significantly higher in the LPS group.…”
Section: Discussionmentioning
confidence: 89%
“…8 Olfactory impairment develops when neuroinflammation occurs in the olfactory bulb in a rat model of experimental stroke. 9 To date, the number of related rhinosinusitis models has been limited and most studies did not include parameters concerning olfactory function. [10][11][12][13][14][15][16][17] Lipopolysaccharides (LPS), one of the major components of the bacterial endotoxin of Gram-negative bacilli, are able to activate neutrophils to induce an immune response and subsequent sinonasal inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Table 1 shows, we observed that the organ coe cient after co-exposure was signi cantly higher than those in the CON group, meaning that there may be pathological injury like brain edema. Then, the buried pellet test, which can evaluate rodents' olfactory function and odor recognition ability, was processed (van Zyl et al, 2016; Lee et al, 2019;Yeh et al, 2019). Olfactory dysfunction can be an essential indicator of learning and memory impairment.…”
Section: Causes Brain Damage In Female Micementioning
confidence: 99%